PENGARUH KOMBINASI PUPUK ORGANIK DAN ANORGANIK TERHADAP PRODUKSI KACANG TANAH (Arachis hypogaea L.) VARIETAS LOKAL BIMA DALAM UPAYA PEMBUATAN BROSUR BAGI MASYARAKAT - Hildegardis Jenira; Sumarjan Sumarjan; Sucika Armiani (Bioscientist : Jurnal Ilmiah Biologi, 2017)
ABSTRACT: This research has been done in the garden address Jln. Lestari, Gg Manalagi IV no.11 Pangkeruk Bangket, Ampenan, Mataram city, from August to November 2016. This research has four factors of perlakauan consisting of first treatment factor (P0) is 100% of land, second (P1) 100% organic fertilizer, third (P2) 50% organic fertilizer + 50% inorganic fertilizer and fourth (P3) 100% of anorganic fertilizer, all of these treatment factors are repeated 4 times so there are 16 experimental units. The experimental design used was Completely Randomized Design (RAL). The data collection technique was done by direct observation and the data obtained were analyzed using ANOVA, which was assisted by using SPSS version 16 for windows. The results showed that the combination of organic and inorganic fertilizers did not have a significant effect on the stem height, the number of branches, the number of pods, the wet weight of the pods and the dry weight of the pod, but significantly influenced the number of plant leaves with F count 3.580> F table 3.29 on direction of 0.5% significance. After Duncan tested the highest tendency of poduksi was obtained on the P2 perlakun factor followed by treatment factor (P1) and treatment factor (P3), then the lowest growth and peanut production were obtained at 100% P (100%) treatment factor.